Functional characterization of the role of the N-terminal domain of the c/Nip1 subunit of eukaryotic initiation factor 3 (eIF3) in AUG recognition - Karásková, Martina; Gunišová, Stanislava; Herrmannová, Anna; Wagner, Susan; Munzarová, Vanda; Valášek, Leoš Shivaya (The Journal of biological chemistry, 2012)
In eukaryotes, for a protein to be synthesized, the 40 S subunit has to first scan the 5'-UTR of the mRNA until it has encountered the AUG start codon. Several initiation factors that ensure high fidelity of AUG recognition were identified previously, including eIF1A, eIF1, eIF2, and eIF5. In addition, eIF3 was proposed to coordinate their functions in this process as well as to promote their initial binding to 40 S subunits. Here we subjected several previously identified segments of the N-terminal domain (NTD) of the eIF3c/Nip1 subunit, which mediates eIF3 binding to eIF1 and eIF5, to semirandom mutagenesis to investigate the molecular mechanism of eIF3 involvement in these reactions. Three major classes of mutant substitutions or internal deletions were isolated that affect either the assembly of preinitiation complexes (PICs), scanning for AUG, or both. We show that eIF5 binds to the extreme c/Nip1-NTD (residues 1-45) and that impairing this interaction predominantly affects the PIC formation. eIF1 interacts with the region (60-137) that immediately follows, and altering this contact deregulates AUG recognition. Together, our data indicate that binding of eIF1 to the c/Nip1-NTD is equally important for its initial recruitment to PICs and for its proper functioning in selecting the translational start site.
Keywords: eukaryotický iniciační faktor 3; Eukaryotic Initiation Factor-3; Saccharomyces cerevisiae; Ribosome Subunits, Small, Eukaryotic; Peptide Chain Initiation, Translational; malé podjednotky ribozomu eukaryotické; kodon iniciační; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae Proteins; iniciace translace peptidového řetězce; Codon, Initiator; Multiprotein Complexes; multiproteinové komplexy